An observational thoracic radiographic study of aortic remodeling in dogs with confirmed systemic hypertension. Issue 3 (5th January 2022) - Holland, Merrilee; Hudson, Judith; Hofmeister, Erik
Abstract: Sustained systemic hypertension (SH) has been shown to cause target organ damage to various tissues in dogs and cats, including the aorta. Aortic dilatation occurs most commonly secondary to SH in people and develops prior to an aortic aneurysm. Our hypothesis was that blinded reviewers could be trained to recognize variable alterations of aortic shape and size on thoracic radiographs of canine patients with SH. A retrospective, observational, cross‐sectional study was performed with three blinded reviewers evaluating thoracic radiographic images of 21 dogs with normal blood pressure compared to 145 dogs with system hypertension. Lateral radiographs showed variable aortic undulation and disproportionate enlargement of a portion of the aorta between the ascending and proximal descending aorta compared to the descending aorta just cranial to the diaphragm. On orthogonal projections, the aortic arch to proximal descending aorta bowed laterally similar to changes reported in people with the formation of an aortic "knob." After completing a training module, reviewers of the thoracic images had a 74% agreement with Fleiss' Kappa of 0.50 indicating moderate agreement recognizing SH changes to the thoracic aorta. The more experienced blinded reviewers had accuracies of 85% and 80% for identifying systemic hypertension, slightly better than the less experienced reviewer at 76%. The ratio of thoracic cavity width to aortic knob width was significantly different between the groups (median ratio 3.4 SH vs 4.1 normal). Evidence of target organ damage (TOD) to the thoracic aorta may prompt earlier recognition and treatment for systemic hypertension.